(untitled) - Kennedy, John F. (New York, 2003)
During 1954-1955, John F. Kennedy, then a U.S. Senator, chose eight of his historical colleagues to profile for their acts of astounding integrity in the face of overwhelming opposition. These heroes include John Quincy Adams, Daniel Webster, Thomas Hart Benton, and Robert A. Taft." "Awarded the Pulitzer Prize in 1957, Profiles in Courage - now reissued in this handsome hard-cover edition, featuring a new introduction by Caroline Kennedy, as well as Robert Kennedy's foreword written for the memorial edition of the volume in 1964 - resounds with timeless lessons on the most cherished of virtues and is a powerful reminder for the strength of the human spirit.
Keywords: Courage,Lòng can đảm